STRATEGI PT. USAHA GUNA MANDIRI DALAM MENGHADAPI PERSAINGAN USAHA JASA PENYEDIA TENAGA KERJA DI KOTA MAKASSAR - Andi Sumarlin K (CV. Adiba Aisha Amira, 2025)
This study aims to determine the application of marketing strategies at PT. Usaha Guna Mandiri and the obstacles faced in competing with similar businesses. This study employs a qualitative descriptive research method, which involves collecting and explaining non- numerical data, which is then compared with relevant theories to obtain clear results that serve as conclusions and recommendations. The data collection methods used include interviews, direct observation, and documentation. To test the credibility of the data, the data source triangulation method and the data collection technique triangulation method were used. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The research participants were the management of PT. Usaha Guna Mandiri, who were able to be used as research data in the interviews. The results of this study indicate that the implementation of marketing strategies and efforts to overcome the challenges faced by PT. Usaha Guna Mandiri in competing with similar businesses is by using the 7P marketing mix strategy, namely product mix by offering a variety of services and high-quality products. Price mix involves offering prices that are affordable according to the UMP/UMK. The place mix involves strategic and easily accessible locations near shopping centres in Makassar with adequate security. The promotion mix includes direct product offerings and social media. The people mix focuses on providing services that prioritise honesty, cleanliness, and neatness. The process mix involves easy, fast, and meticulous transaction processes. The physical evidence mix highlights the appeal of experienced workers and straightforward processes